2019
DOI: 10.1177/1463499618807294
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberalism at work: Corporate reforms, subjectivity, and post-Toyotist affect in Japan

Abstract: This article analyzes how the Japanese state and corporations promoted neoliberal restructuring and how employees responded to and reflected upon such changes. I show how neoliberal reforms have aimed to produce greater flexibility for corporations and promote a specific mode of control—“self-management”—among employees. However, rather than rationalizing and legitimizing risk and becoming self-regulating “enterprising selves,” many employees displayed a reflexive and reactive subjectivity that eschewed such n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…48 For example, Japanese women faced unprofitable income due to the government tax policies and company, so they prefer to be at home and the husband providing salary and benefits. 53 Both nations are driven by patriarchal, masculine values, whereby domestic responsibilities should be a woman's foremost priority. 54,55 Therefore, Tlaiss 49 and Yamazaki et al 48 reported that organizational barriers to female doctors were only an extension of larger socio-cultural expectations.…”
Section: Stereotypingmentioning
confidence: 99%
“…48 For example, Japanese women faced unprofitable income due to the government tax policies and company, so they prefer to be at home and the husband providing salary and benefits. 53 Both nations are driven by patriarchal, masculine values, whereby domestic responsibilities should be a woman's foremost priority. 54,55 Therefore, Tlaiss 49 and Yamazaki et al 48 reported that organizational barriers to female doctors were only an extension of larger socio-cultural expectations.…”
Section: Stereotypingmentioning
confidence: 99%
“…Competition is one of the key ideologies that promotes (neoliberal) capitalism, primarily through organization (or imposition) of markets (Carrier 1997), although, according to neoliberal doctrine, the markets need to be actively regulated in order to render competition ‘beneficial’ and ‘fair’ (Hayek, quoted in Gershon 2011: 541). Opening up places to markets does not necessarily create atomized individualistic subjects focused on efficiency, performance, and self‐improvement (Ferguson 2010; Okura Gagné 2020), but it certainly creates new situations in which people subjected (or drawn) to the market need to negotiate between the demands of the competitive market and the demands of ‘moral economies’ (J.C. Scott 1976) in which they continue to be immersed. Considering competition as a ‘structural relationship among competitors’ (Colloredo‐Mansfeld 2002: 113) is therefore useful: it complicates the view of markets as collections of individualized subjects compelled to compete amongst each other for the sole sake of profit.…”
Section: Figurementioning
confidence: 99%
“…This work has largely been inspired by Foucault (1982Foucault ( , 1991 and his attention to the relationship between subjectivity and structure, rather than Bateson. In everything from state-sponsored and corporate sporting events (Besnier et al 2018;Walker 2013) to labor regimes (Gershon 2011;Okura Gagné 2020;Urciuoli 2008) and knowledge economies (Chong 2020), competition is increasingly identifi ed as the subjectifying force that shapes collectives of atomized, self-centered individuals.…”
Section: Structure Inequality and Subjectivitymentioning
confidence: 99%
“…The anthropologies of work and neoliberalism critique neoliberal visions of competition as a universalizing mechanism that encourages subjects to imagine themselves as a "bundle of skills" (Urciuoli 2008: 215) that must be constantly and refl exively improved, and to act rationally in a shared yet agonistic pursuit of maximal fi nancial profi t (Gershon 2011;Mirowski 2013;Rose 1996). Recent ethnography has emphasized the damaging effects of competition as a technique of neoliberal governance and subjectivation (Chong 2020;Li 2007;Okura Gagné 2020;Tooley 2017), one that atomizes subjects, corrodes solidarity, and reproduces established hierarchies of wealth and power. The prevalence of this critique has, however, sidelined attention to competition in its own right as an object of ethnographic comparison.…”
mentioning
confidence: 99%